Tax Behaviour: Assessment of Tax Compliance in European Union Countries - Pukeliene, Violeta; Kažemekaityte, Austeja (Ekonomika, 2016)
The aim of this paper is to assess the impact of the selected tax behaviour determinants for the overall tax (non) compliance in European Union countries for a period from 2003 to 2014. Firstly, the literature on tax behaviour is analysed through the viewpoint of behavioural economics and the systemisation of the main determinants is provided. Secondly, selected tax behaviour determinants for the analysis are presented, hypotheses raised and models formed. Research suggests that tax morale, socio-cultural determinants and the relationship between tax authority and taxpayers have an overall significant impact on tax behaviour in European Union countries. Nevertheless, the effect from different determinants varies greatly across regions and countries.
Keywords: tax compliance; tax evasion; tax behaviour; slippery slope framework; tax morale; tax culture